Analisis Dampak Kualitas Laba terhadap Hubungan Antara Readability dan Cost of Capital - Mar Atu Syarifah; Nurzi Sebrina (Universitas Negeri Padang, 2024)
The purpose of this study is to explore the relationship between disclosure quality, measured by the readability of the board of director report and cost of capital, and attempt to investigate the moderating effect of earning quality on relationship between readability and cost of capital. The population in this study are manufacture companies listed on Indonesian Stock Exchange in 2018-2022. The research uses purposive sampling technique to obtain research samples. The data analysis technique in this study used moderating regression analysis using the Eviews12 program. The result showed that readability of board of director reports does not impact on cost of capital. In addition, after moderating by earning quality, there is a significant association between readability and cost of capital.